Social Work Method and Ideology Work Innovation Based on Talent Three-Dimensional Ability Model - Hao Zheng,Chuan-yuan Peng (Design Engineering, 2021)
With the diversification of economic components and lifestyles in the process of social transformation, the introduction and application of social work values and methods in ideology education can effectively enrich the content of ideology education, improve the way of ideology education and improve the effect of ideology work. In ideology education, we can effectively enrich the content, improve the way and improve the effect of ideology education by using the concepts of equal treatment, service and self-determination of the educated in social work for reference. This paper analyzes the role of talents' three-dimensional ability model in the innovation of Chinese social work methods and ideology work, and discusses how to improve the overall quality of social work talents by perfecting the management mechanism of social work talents selection, training and performance based on the quality model.